Prevalence of contact allergy in the general population: A systematic review and meta‐analysis - Alinaghi, Farzad; Bennike, Niels H.; Egeberg, Alexander; Thyssen, Jacob P.; Johansen, Jeanne D. (Contact dermatitis, 2019)
Background Contact allergy and allergic contact dermatitis are frequent conditions in the general population. Objectives To provide an updated estimate of the prevalence of contact allergy in the general population based on data from our previous review combined with new data from an updated search for relevant studies published between 2007 and 2017. Methods Two authors independently searched PubMed for studies reporting on the prevalence of contact allergy in samples of the general population. Proportion meta‐analyses were performed to calculate the pooled prevalence estimates of contact allergy. Results A total of 28 studies were included in the analysis, covering 20 107 patch tested individuals from the general population. Overall, the pooled prevalence of contact allergy was 20.1% (95% confidence interval [CI]: 16.8%‐23.7%). In children and adolescents (<18 years), the prevalence was 16.5% (95%CI: 13.6%‐19.7%). The prevalence was significantly higher in women (27.9% [95%CI: 21.7%‐34.5%]) than in men (13.2% [95%CI: 9.3%‐17.6%]). The most common allergen was nickel (11.4% [95%CI: 9.4%‐13.5%]), followed by fragrance mix I (3.5% [95%CI: 2.1%‐5.4%]), cobalt (2.7% [95%CI: 2.1%‐3.4%]), Myroxylon pereirae (1.8% [95%CI: 1.0%‐2.7%]), chromium (1.8% [95%CI: 1.3%‐2.6%]), p‐phenylenediamine (1.5% [95%CI: 1.0%‐2.1%]), methylchloroisothiazolinone/methylisothiazolinone (1.5% [95%CI: 0.8%‐2.5%]), and colophonium (1.3% [95%CI: 1.0%‐1.6%]). Conclusions This meta‐analysis confirmed that at least 20% of the general population are contact‐allergic to common environmental allergens. It highlights the need for more effective preventive strategies for common allergens in consumer goods, cosmetics, and the workplace.